2021
DOI: 10.35848/1347-4065/abf6e7
|View full text |Cite
|
Sign up to set email alerts
|

Schottky barrier diodes fabricated on high-purity type-IIa CVD diamond substrates using an all-ion-implantation process

Abstract: We fabricated a Schottky barrier diode (SBD) on ion-implanted diamond substrates. The SBDs contained lightly doped regions under the Schottky electrodes and heavily doped regions beneath the Ohmic contacts. The current remained below 6.4 × 10−11 A at reverse biases of up to 10 V, but increased sharply at a forward bias of −3.5 V. The Schottky barrier height and ideality factor under forward bias were estimated to be 1.1 eV and 10, respectively. The hole concentrations obtained by measuring the capacitance at v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The Schottky barrier height is almost the same as that for previously reported diamond SBD with Al as the Schottky metal contact fabricated by the ion implantation technique. 26) Schottky barrier heights observed for SBD devices fabricated with Albased electrodes formed on CVD-boron-doped diamond film reported by Teraji et al were ranging from 1.01 to 1.28 eV. 32) Comparing the previous results obtained from implantationdoping, a significant difference is not observed in the barrier height value.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…The Schottky barrier height is almost the same as that for previously reported diamond SBD with Al as the Schottky metal contact fabricated by the ion implantation technique. 26) Schottky barrier heights observed for SBD devices fabricated with Albased electrodes formed on CVD-boron-doped diamond film reported by Teraji et al were ranging from 1.01 to 1.28 eV. 32) Comparing the previous results obtained from implantationdoping, a significant difference is not observed in the barrier height value.…”
mentioning
confidence: 91%
“…According to our previous report, the ideality factor was over than 10. 26) It is therefore suggested that the present device has significantly improved the electronic properties, though there are still some crucial points to improve SBD properties.…”
mentioning
confidence: 91%
See 3 more Smart Citations